Object-oriented application framework for statistical process control in manufacturing domain / Liu Hong Song - Liu , Hong Song (2004)
A continuing challenge for software developers is to design and develop efficient and cost-effective software implementation. Designing and developing new manufacturing applications is even time consuming and expensive due to the nature of manufacturing domain, which is diverse and complex. Using an object-oriented application framework is a promising means for alleviating this cost. An object-oriented application framework is a reusable software component providing large-scale reuse, which could include reuse of analysis, design and implementation in order to develop software faster to market. The main objective of this research is to provide a solution by developing an object-oriented manufacturing application framework in the domain of Statistical Process Control (SPC), with a set of integrated reusable components, which can be customised to suit specific SPC manufacturing applications. This application framework provides a solution for developers to produce specific manufacturing applications by making use of existing integrated reusable components rather than developing these applications from scratch. Based on the structure and behaviour of various SPC applications, a generic model of SPC is proposed by following the concept of object-oriented technology, software component technology and design pattern. This dissertation will describe in detail the architecture and design in the development of the application framework for statistical process control in the manufacturing domain.